Genomic and Phenotypic Analyses of Acinetobacter baumannii Isolates From Three Tertiary Care Hospitals in Thailand - Loraine, Jessica; Heinz, Eva; Soontarach, Rosesathorn; Blackwell, Grace A.; Stabler, Richard A.; Voravuthikunchai, Supayang P.; Srimanote, Potjanee; Kiratisin, Pattarachai; Thomson, Nicholas R.; Taylor, Peter W. (Frontiers in Microbiology, 2020)
Antibiotic resistant strains of Acinetobacter baumannii are responsible for a large and increasing burden of nosocomial infections in Thailand and other countries of Southeast Asia. New approaches to their control and treatment are urgently needed and we are actively seeking biological agents that remove the polysaccharide capsules that protect these pathogens from the host’s immune system. To examine phylogenetic relationships, distribution of capsule chemotypes, acquired antibiotic resistance determinants, susceptibility to complement and other traits associated with systemic infection, we sequenced 191 recent isolates from three tertiary referral hospitals in Thailand and used phenotypic assays to characterise key aspects of infectivity. Several distinct lineages were circulating in three hospitals and the majority belonged to global clonal group 2 (GC2). Very high levels of resistance to carbapenems and other front-line antibiotics were found, as were a number of widespread plasmid replicons. A high diversity of capsule genotypes were encountered with only three (KL6, KL10 and KL47) above 10% frequency. Almost 90% of GC2 isolates belonged to the most common capsule genotypes and were fully resistant to the bactericidal action of human serum complement; we attribute this trait to the presence of a substantial protective capsule and for this to represent a key determinant of virulence for systemic infection. We conclude that current Thai nosocomial isolates represent potential targets for therapeutic strategies designed to remove the polysaccharide capsule from extensively drug-resistant A. baumanii during the course of systemic infection.